2021
DOI: 10.3390/metabo11060380
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis Modulates the Gut Microbiome and Metabolism in a Murine Infection Model

Abstract: Cryptosporidiosis is a major human health concern globally. Despite well-established methods, misdiagnosis remains common. Our understanding of the cryptosporidiosis biochemical mechanism remains limited, compounding the difficulty of clinical diagnosis. Here, we used a systems biology approach to investigate the underlying biochemical interactions in C57BL/6J mice infected with Cryptosporidium parvum. Faecal samples were collected daily following infection. Blood, liver tissues and luminal contents were colle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…In this study, we showed that giardiasis results in greater expression of energy and associated pathways in the duodenumjejunum and colon. This was somewhat different to the mechanism during cryptosporidiosis, where these pathways were greatly upregulated in the jejunum-ileum [23,24]. It has been shown that the microaerophilic nature of Giardia aids in modulating the energy pathways during increased oxygen tension [12].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we showed that giardiasis results in greater expression of energy and associated pathways in the duodenumjejunum and colon. This was somewhat different to the mechanism during cryptosporidiosis, where these pathways were greatly upregulated in the jejunum-ileum [23,24]. It has been shown that the microaerophilic nature of Giardia aids in modulating the energy pathways during increased oxygen tension [12].…”
Section: Discussionmentioning
confidence: 92%
“…Microbial, protein and metabolic extractions from luminal washes, blood serum and liver were performed as per the protocols reported previously [24] without any modifications. Amplicons were generated from the V3 and V4 regions of 16S rRNA using genespecific primers.…”
Section: Microbiome Proteomics and Metabolome: Extraction And Processingmentioning
confidence: 99%
“…survival in the hosts’ gut must interact with intestinal constituents to compensate for deficiencies, i.e., lack of numerous metabolic systems ( Alcock et al, 2012 ). Gut microbiome–parasite relationship was demonstrated to be a medium in modulating significant biochemical changes during cryptosporidiosis ( Karpe et al, 2021 ). Charania et al (2020) identified that specific changes in the gut microbiome allow for more favorable survival of Cryptosporidium parasite in mice ( Charania et al, 2020 ), hence this conclusion supported the current results.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, the impact of microbial consortia in the parasite-epithelial host cell interaction needs to be recognized, and more comprehensive approaches are required in order to address such complex multispecies interactions [22,75].…”
Section: Discussionmentioning
confidence: 99%